GREEN SYNTHESIS OF DIFFERENT NANOPARTICLES AND THEIR POTENTIAL APPLICATIONS IN DIFFERENT FIELDS- A CRITICAL REVIEW - CHANDRA KANT SHARMA,; MONIKA SHARMA,; OSHIN VERMA,; VINAY SHARMA, (International Journal of Pharma and Bio Sciences, 2015)
Nanoparticles (NPs) as its name suggests is a ‘nano’ or ‘dwarf’ particle with size ranges from 1nm to 100 nm. NPs synthesis and characterization is done under the field of ‘Nanotechnology’ which is one of the promising field of science, deals with small dimension material and have potential impact in all field of human life. NPs have broad range of application in electronics, environment and in medical field for drug and gene delivery. Traditionally, different methods have been extensively employed by researchers for NPs fabrication, but chemical as well as physical methods are not suitable due to hazardous chemicals, high cost, and intense labor. Therefore Green Nanotechnology’ is used to resolve these drawbacks ‘which use plants for NPs synthesis. Green synthesis of NPs reduce the contamination from environment and preserve natural resources, it is cost effective and faster technique that helps in large scale production of NPs. Green Synthesis of NPs from plants depends on the reducing capacity of plants to reduce metal ions. After synthesis of NPs its shape and size characterized by various techniques like UV-VIS spectroscopy, EPMA (Electron Probe Micro Analysis), XRD (X-ray Diffraction), Zeta potential and FTIR (Fourier Transform Infrared) analysis. NPs also have antimicrobial activity which is examined against various microorganisms.